Report of the Committee on Banks relative to the currency, &c. &c. &c. (House document (Virginia. General Assembly. House of Delegates), 1863)
1863 Report of the Committee on Banks regarding a resolution concerning currency. The committee put forth four resolutions that reiterated its loyalty to the Confederacy and encouraged a law to create corporate bodies to invest in the stock of the Confederate government, and individuals likewise be encouraged to do the same.